Immersed nanometer cycle fluid based on alkyl modified polysiloxane
By using nanocyclic working fluid based on alkyl modified polysiloxane in the immersed cooling working fluid and adding nanoparticles and surfactants, the problems of low heat dissipation efficiency and high risk of thermal runaway in the prior art are solved, and the performance improvement of efficient heat transfer, anti-freeze, insulation and anti-fire performance is achieved.
Patent Information
- Application Number
- CN202510017826.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The immersive cooling working fluid in the prior art has low heat dissipation efficiency and high risk of thermal runaway, and cannot meet the problems of efficient heat transfer, anti-freeze, insulation and anti-fire performance at the same time.
Using an immersed nanocirculating working fluid based on alkyl modified polysiloxane, nanofluids were formed to improve thermal conductivity and anti-corrosion and precipitation properties by adding 0.005-11.5% nanoparticle mixture, 88.0%-99.5% alkyl modified polysiloxane liquid, 0.05-0.09% dispersant and 0.5-15% cosurfactant.
It significantly improves the thermal conductivity and corrosion and precipitation properties of nano-circulating working fluids, enhances the enhanced flow boiling heat exchange effect between the PACK inside and outside of the lithium iron phosphate battery, and solves the problems of low heat dissipation efficiency and high risk of thermal runaway.
Smart Images

Figure CN119650972A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy lithium iron phosphate batteries, and in particular to an immersion-type nano-circulation working fluid based on alkyl-modified polysiloxane. Background Art
[0002] With the vigorous development of the new energy industry, lithium iron phosphate batteries have been widely used in the field of renewable energy storage due to their advantages of long life, low self-discharge rate and high energy density. However, under certain conditions, such as high-rate charging and discharging, narrow battery spacing and high temperature environment, lithium iron phosphate batteries are prone to accumulate heat, resulting in increased battery temperature. It is worth noting that the electrochemical properties of lithium iron phosphate batteries are highly sensitive to their operating temperature. Increased temperature will not only accelerate the aging process of the battery, but may also cause the risk of thermal runaway of the battery. In addition, uneven temperature distribution inside the battery PACK will also cause different degrees of battery aging, and SOC (remaining charge) and SOH (health state) will drop rapidly, which may aggravate the aging of the electrical system and bring potential safety hazards.
[0003] In response to the heat dissipation problem of lithium iron phosphate batteries, traditional heat exchange systems, such as phase change material heat absorption, bottom liquid cooling plate heat absorption, air cooling and their combination, have alleviated the heat dissipation problem to a certain extent, but have not completely solved the heat dissipation and safety problems of lithium iron phosphate batteries. In contrast, immersion liquid cooling technology stands out with its compact design, excellent heat dissipation efficiency and ability to prevent battery thermal runaway, especially under high-rate cycle conditions, immersion liquid cooling has become the only solution to meet the heat dissipation needs of battery PACK. However, the heat dissipation efficiency of immersion liquid cooling is highly dependent on the selection of cooling media and the internal structure design of the system.
[0004] The immersion cooling medium in the prior art has the problems of low heat dissipation efficiency, high risk of thermal runaway, and failure to simultaneously meet the requirements of efficient heat transfer, antifreeze, insulation and fire prevention performance. Summary of the invention
[0005] The purpose of the present invention is to provide an immersion nano-circulation working fluid based on alkyl-modified polysiloxane, aiming to solve the technical problems of low heat dissipation efficiency, high risk of thermal runaway, and inability to simultaneously meet the requirements of efficient heat transfer, antifreeze, insulation and fire prevention in the immersion cooling working fluid in the prior art.
[0006] To achieve the above-mentioned purpose, the present invention adopts an alkyl-modified polysiloxane-based immersed nano-circulation working fluid, which includes 0.005-11.5% of a nanoparticle mixture, 88.0%-99.5% of an alkyl-modified polysiloxane base liquid, 0.05-0.09% of a dispersant and 0.5-15% of a co-surfactant;
[0007] The nanoparticle mixture includes γ-Al2O3 nanoparticles and SiO2 nanoparticles.
[0008] The nanoparticle mixture has a particle size of 10-100 nm and a purity of 99.9%.
[0009] Wherein, the dispersant is one of a zwitterionic surfactant and a nonionic surfactant.
[0010] Wherein, the co-surfactant is a mixture of butanol and acrylamide in a ratio of 1:2.
[0011] Wherein, the dispersant zwitterionic surfactant includes dodecyl betaine, dodecyl propyl betaine and alkyl glycoside.
[0012] Wherein, the dispersant nonionic surfactant is polyvinyl pyrrolidone.
[0013] The present invention also provides a method for preparing an alkyl-modified polysiloxane-based immersed nano-circulation working fluid, which is used to prepare the alkyl-modified polysiloxane-based immersed nano-circulation working fluid as described above.
[0014] Step 1, first obtain an alkyl-modified polysiloxane base liquid for use;
[0015] Step 2: adding the dispersant and the co-surfactant to the alkyl-modified polysiloxane respectively and stirring evenly to obtain a mixed organic matter;
[0016] Step 3: Finally, the nanoparticle mixture is added to the mixed organic matter, and ultrasonically oscillated for 5-24 hours at a frequency of 25-60 KHz to obtain an immersion nano-circulation working fluid based on alkyl-modified polysiloxane.
[0017] Wherein, in step 2, the dispersant and the co-surfactant are respectively added to the alkyl-modified polysiloxane and stirred evenly to obtain a mixed organic matter:
[0018] The stirring time is 30-180 minutes, and after the mixing is completed, it is allowed to stand for 30-60 minutes.
[0019] The invention discloses an immersion type nano-circulation working fluid based on alkyl-modified polysiloxane, comprising 0.005-11.5% of a nano-particle mixture, 88.0%-99.5% of an alkyl-modified polysiloxane base liquid, 0.05-0.09% of a dispersant and 0.5-15% of a co-surfactant; the nano-particle mixture comprises γ-Al2O3 nano-particles and SiO2 nano-particles, and the alkyl-modified polysiloxane base liquid is firstly obtained for standby use; then the dispersant and the co-surfactant are respectively added to the alkyl-modified polysiloxane and stirred evenly to obtain a mixed organic matter; finally, the nano-particle mixture is added to the mixed organic matter, and ultrasonic oscillation is performed for 5-24 hours under a frequency of 25-60KHz to obtain an immersion type nano-circulation working fluid based on alkyl-modified polysiloxane, thereby solving the technical problems of low heat dissipation efficiency, high risk of thermal runaway, and failure to simultaneously meet the requirements of high-efficiency heat transfer, antifreeze, insulation and fire prevention in the immersion cooling working fluid in the prior art.
[0020] The present invention modifies polysiloxane, adds a dispersant and a co-surfactant, and adds γ-Al2O3 and SiO2 nanoparticles with a particle size of 10nm and a purity of 99.9% to the formed new mixture, thereby effectively improving the thermal conductivity and anti-corrosion and anti-precipitation properties of the nano-circulating working fluid. The prepared nano-circulating working fluid is suitable for immersion equipment.
[0021] In the immersed nano-circulation working fluid of the alkyl-modified polysiloxane prepared by the present invention, in the nanofluid, the suspended nanoparticles are acted upon by various forces such as Brownian force, thereby generating irregular diffusion; these diffusion phenomena include Brownian diffusion and thermal diffusion, etc.; the tiny movement of the nanoparticles leads to micro-convection between the particles and the liquid, and the micro-convection strengthens the energy transfer between the particles and the liquid, thereby improving the heat transfer efficiency per unit area of the nanofluid.
[0022] Since the thermal conductivity of solid nanoparticles is much better than that of liquids, the addition of the selected non-conductive nanoparticles changes the microstructure of the alkyl-modified polysiloxane base liquid, promotes the energy transfer of the nano-circulating working fluid coolant inside the lithium iron phosphate battery PACK, improves the thermal conductivity and Prandtl number, and significantly enhances the enhanced flow boiling heat transfer effect between the inside and outside of the lithium iron phosphate battery PACK. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 It is a flow chart of the steps of the preparation method of the submerged nano-circulation working fluid based on alkyl-modified polysiloxane of the present invention. DETAILED DESCRIPTION
[0025] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0026] The invention provides an immersion type nanometer circulation working fluid based on alkyl modified polysiloxane, comprising 0.005-11.5% of a nanometer particle mixture, 88.0%-99.5% of an alkyl modified polysiloxane base liquid, 0.05-0.09% of a dispersant and 0.5-15% of a cosurfactant;
[0027] The nanoparticle mixture includes γ-Al2O3 nanoparticles and SiO2 nanoparticles.
[0028] The nanoparticle mixture has a particle size of 10-100 nm and a purity of 99.9%.
[0029] Wherein, the dispersant is one of a zwitterionic surfactant and a nonionic surfactant.
[0030] Wherein, the co-surfactant is a mixture of butanol and acrylamide in a ratio of 1:2.
[0031] Wherein, the dispersant zwitterionic surfactant includes dodecyl betaine, dodecyl propyl betaine and alkyl glycoside.
[0032] Wherein, the dispersant nonionic surfactant is polyvinyl pyrrolidone.
[0033] See also Figure 1 , Figure 1 It is a flow chart of the steps of the preparation method of the submerged nano-circulation working fluid based on alkyl-modified polysiloxane of the present invention.
[0034] The present invention also provides a method for preparing an alkyl-modified polysiloxane-based immersed nano-circulation working fluid, which is used to prepare the alkyl-modified polysiloxane-based immersed nano-circulation working fluid as described above.
[0035] Step 1, first obtain an alkyl-modified polysiloxane base liquid for use;
[0036] Step 2: adding the dispersant and the co-surfactant to the alkyl-modified polysiloxane respectively and stirring evenly to obtain a mixed organic matter;
[0037] Step 3: Finally, the nanoparticle mixture is added to the mixed organic matter, and ultrasonically oscillated for 5-24 hours at a frequency of 25-60 KHz to obtain an immersion nano-circulation working fluid based on alkyl-modified polysiloxane.
[0038] Wherein, in step 2, the dispersant and the co-surfactant are respectively added to the alkyl-modified polysiloxane and stirred evenly to obtain a mixed organic matter:
[0039] The stirring time is 30-180 minutes, and after the mixing is completed, it is allowed to stand for 30-60 minutes.
[0040] Embodiment 1:
[0041] In this embodiment, the mass percentages of the components of the alkyl-modified polysiloxane-based submerged nano-circulation working fluid are: 96.5% alkyl-modified polysiloxane base liquid, 3% nanoparticle mixture with a particle size of 100 nm (including γ-Al2O3 nanoparticles and SiO2 nanoparticles), 0.5% dispersant, and 1% surfactant.
[0042] The preparation method is as follows:
[0043] First, add 100 parts by weight of high-boiling organosilicon into the reaction kettle at 20°C-25°C, then dropwise add 30-40 parts by weight of raw material methanol with a weight percentage of 80%-90%, and dropwise add for 6-8 hours. The initial dropwise addition rate is 3 parts / hour, and gradually increases to 10 parts / hour after 2-3 hours of dropwise addition. The hydrogen chloride gas generated during the alcoholysis process is absorbed by spraying water to form solution A.
[0044] Then, 15-18 parts by weight of methanol as a co-solvent and an equal amount of urea are gradually added to solution A, and the neutralization temperature is 42°C-50°C, and the neutralization time is 0.5 hours to neutralize the hydrochloric acid in the material. After layering, a crude high-boiling silicone oil is obtained, and the pH value is 4-5. Then, 1.0-1.5 parts by weight of 27% ammonia water is added, and the neutralization is continued to make the pH value 6-8;
[0045] Subsequently, the neutralized solution A is filtered and then the first olefin is added dropwise to carry out a first heat preservation reaction; chloroplatinic acid catalyst is added, and the second olefin is added dropwise to carry out a second heat preservation reaction; after distillation, an alkyl-modified polysiloxane alkane liquid is obtained;
[0046] Then, the dispersant and the co-surfactant are respectively added to the prepared alkyl-modified polysiloxane base liquid and stirred evenly to obtain a mixed organic matter; (the stirring time is 15 minutes; the dispersant is dodecyl betaine, the co-surfactant is a mixture of butanol and acrylamide in a ratio of 1:2, the volume ratio of the dispersant to the co-surfactant is 40:60, and the amount of the stabilizer composed of the dispersant and the co-surfactant is 1.5% of the mass of the immersed nano-circulation working fluid; the amount of the alkyl-modified polysiloxane base liquid added is 96.5% of the mass of the immersed nano-circulation working fluid);
[0047] Finally, the nanoparticle mixture is added to the mixed organic matter, ultrasonically oscillated for 5 hours at a frequency of 25KHz, and then left to stand for 12 hours to obtain an immersion nano-circulation working fluid based on alkyl-modified polysiloxane. (Through high-precision mechanical grinding, and then through oxidation, pyrolysis, plasma, laser ablation, laser pyrolysis and other methods, the core is formed in the steam and finally crystallized to form γ-Al2O3 nanoparticles, and the same method is used to form SiO2 nanoparticles. The two nanoparticles are shaken and stirred and mixed in a plasma ultrasonic oscillator at a frequency of 25KHz. The shaking and stirring mixing time is 10 hours to obtain a nanoparticle mixture, that is, a stable γ-Al2O3 and SiO2 mixed organic nanoparticles)
[0048] The immersed nano-circulating working fluid of the alkyl-modified polysiloxane prepared in this embodiment has the properties of high thermal conductivity and increased Prandtl number during the flow heat exchange process. At the same time, the addition of nanoparticles breaks the flow wall boundary between the alkyl-modified polysiloxane base liquid and the tube wall, which greatly increases the disturbance-enhanced heat transfer. According to the analysis of the measuring points, the prepared immersed nano-circulating working fluid of the alkyl-modified polysiloxane has an 11% increase in unit heat transfer efficiency and a 40% increase in thermal conductivity compared with pure polysiloxane. According to the analysis of multiple experimental measuring points. The thermal conductivity increases from 0.11W / mK of the original polysiloxane base liquid to 0.15W / mK; the kinematic viscosity increases from 10mm 2 / s reduced to 8mm 2 / s; specific heat capacity increased from 1.6J / kg℃ to 1.7J / kg℃.
[0049] Embodiment 2:
[0050] In this embodiment, the mass percentages of the components of the alkyl-modified polysiloxane-based submerged nano-circulation working fluid are: 94.5% of alkyl-modified polysiloxane base liquid, 4% of a mixture of nanoparticles with a particle size of 100 nm (including γ-Al2O3 nanoparticles and SiO2 nanoparticles), 0.8% of a dispersant, and 0.7% of a surfactant.
[0051] The preparation method is as follows:
[0052] Firstly, obtain an alkyl-modified polysiloxane base liquid for use;
[0053] Then, the dispersant and the co-surfactant are respectively added to the prepared alkyl-modified polysiloxane base liquid and stirred evenly to obtain a mixed organic matter; (the stirring time is 15 minutes; the alkyl-modified polysiloxane base liquid is purchased and provided by Jiangxi Qiantai New Materials Co., Ltd., wherein the dispersant is dodecyl betaine, the co-surfactant is a mixture of butanol and acrylamide in a ratio of 1:2, the volume ratio of the dispersant to the co-surfactant is 40:60, and the amount of the stabilizer composed of the dispersant and the co-surfactant is 1.5% of the mass of the immersed nano-circulation working fluid; the amount of the alkyl-modified polysiloxane base liquid added is 94.5% of the mass of the immersed nano-circulation working fluid)
[0054] Finally, the nanoparticle mixture is added to the mixed organic matter, ultrasonically oscillated for 5 hours at a frequency of 25KHz, and then left to stand for 12 hours to obtain an immersion nano-circulation working fluid based on alkyl-modified polysiloxane. (Through high-precision mechanical grinding, and then through oxidation, pyrolysis, plasma, laser ablation, laser pyrolysis and other methods, the core is formed in the steam and finally crystallized to form γ-Al2O3 nanoparticles, and the same method is used to form SiO2 nanoparticles. The two nanoparticles are shaken and stirred and mixed in a plasma ultrasonic oscillator at a frequency of 25KHz. The shaking and stirring mixing time is 10 hours to obtain a nanoparticle mixture, that is, a stable γ-Al2O3 and SiO2 mixed organic nanoparticles)
[0055] The prepared alkyl-modified polysiloxane immersed nano-circulating working fluid has high thermal conductivity and increased Prandtl number during the flow heat exchange process. At the same time, the addition of nanoparticles breaks the flow wall boundary between the alkyl-modified polysiloxane base liquid and the tube wall, which greatly increases the disturbance-enhanced heat transfer. According to the analysis of the measuring points, the prepared alkyl-modified polysiloxane immersed nano-circulating working fluid has a 15% increase in unit heat transfer efficiency and a 50% increase in thermal conductivity compared with pure polysiloxane. According to the analysis of multiple experimental measuring points. The thermal conductivity increases from 0.11W / mK of the original polysiloxane base liquid to 0.18W / mK; the kinematic viscosity increases from 10mm 2 / s reduced to 9mm 2 / s; specific heat capacity increased from 1.6J / kg℃ to 1.8J / kg℃.
[0056] Embodiment 3:
[0057] In this embodiment, the mass percentages of the components of the alkyl-modified polysiloxane-based submerged nano-circulation working fluid are: 97% alkyl-modified polysiloxane base liquid, 2% nanoparticle mixture with a particle size of 100 nm (including γ-Al2O3 nanoparticles and SiO2 nanoparticles), 0.4% dispersant, and 0.6% surfactant.
[0058] The preparation method is as follows:
[0059] First, add 100 parts by weight of high-boiling organosilicon into the reaction kettle at 20°C-25°C, then dropwise add 30-40 parts by weight of raw material methanol with a weight percentage of 80%-90%, and dropwise add for 6-8 hours. The initial dropwise addition rate is 3 parts / hour, and gradually increases to 10 parts / hour after 2-3 hours of dropwise addition. The hydrogen chloride gas generated during the alcoholysis process is absorbed by spraying water to form solution A.
[0060] Then, 15-18 parts by weight of methanol as a co-solvent and an equal amount of urea are gradually added to solution A, and the neutralization temperature is 42°C-50°C, and the neutralization time is 0.5 hours to neutralize the hydrochloric acid in the material. After layering, a crude high-boiling silicone oil is obtained, and the pH value is 4-5. Then, 1.0-1.5 parts by weight of 27% ammonia water is added, and the neutralization is continued to make the pH value 6-8;
[0061] Subsequently, the neutralized solution A is filtered and then the first olefin is added dropwise to carry out a first heat preservation reaction; chloroplatinic acid catalyst is added, and the second olefin is added dropwise to carry out a second heat preservation reaction; after distillation, an alkyl-modified polysiloxane alkane liquid is obtained;
[0062] Then, the dispersant and the co-surfactant are respectively added to the prepared alkyl-modified polysiloxane base liquid and stirred evenly to obtain a mixed organic matter; (the stirring time is 15 minutes; the dispersant is dodecyl betaine, the co-surfactant is a mixture of butanol and acrylamide in a ratio of 1:2, the volume ratio of the dispersant to the co-surfactant is 40:60, and the amount of the stabilizer composed of the dispersant and the co-surfactant is 1% of the mass of the immersed nano-circulation working fluid; the amount of the alkyl-modified polysiloxane base liquid added is 97% of the mass of the immersed nano-circulation working fluid);
[0063] Finally, the nanoparticle mixture is added to the mixed organic matter, ultrasonically oscillated for 5 hours at a frequency of 25KHz, and then left to stand for 12 hours to obtain an immersion nano-circulation working fluid based on alkyl-modified polysiloxane. (Through high-precision mechanical grinding, and then through oxidation, pyrolysis, plasma, laser ablation, laser pyrolysis and other methods, the core is formed in the steam and finally crystallized to form γ-Al2O3 nanoparticles, and the same method is used to form SiO2 nanoparticles. The two nanoparticles are shaken and stirred and mixed in a plasma ultrasonic oscillator at a frequency of 25KHz. The shaking and stirring mixing time is 10 hours to obtain a nanoparticle mixture, that is, a stable γ-Al2O3 and SiO2 mixed organic nanoparticles)
[0064] The prepared alkyl-modified polysiloxane immersed nano-circulating working fluid has the properties of high thermal conductivity and increased Prandtl number during the flow heat exchange process. At the same time, the addition of nanoparticles breaks the flow wall boundary between the alkyl-modified polysiloxane base liquid and the tube wall, which greatly increases the disturbance-enhanced heat transfer. According to the analysis of the measuring points, the prepared alkyl-modified polysiloxane immersed nano-circulating working fluid has a 6% increase in unit heat transfer efficiency and a 20% increase in thermal conductivity compared with pure polysiloxane. According to the analysis of multiple experimental measuring points. The thermal conductivity increases from 0.11W / mK of the original polysiloxane base liquid to 0.125W / mK; the kinematic viscosity increases from 10mm 2 / s reduced to 9.8mm 2 / s; specific heat capacity increased from 1.6J / kg℃ to 1.63J / kg℃.
[0065] Embodiment 4:
[0066] In this embodiment, the mass percentages of the components of the alkyl-modified polysiloxane-based submerged nano-circulation working fluid are: 94% alkyl-modified polysiloxane base liquid, 4.5% nanoparticle mixture with a particle size of 100 nm (including γ-Al2O3 nanoparticles and SiO2 nanoparticles), 1% dispersant, and 0.5% surfactant.
[0067] The preparation method is as follows:
[0068] First, add 100 parts by weight of high-boiling organosilicon into the reaction kettle at 20°C-25°C, then dropwise add 30-40 parts by weight of raw material methanol with a weight percentage of 80%-90%, and dropwise add for 6-8 hours. The initial dropwise addition rate is 3 parts / hour, and gradually increases to 10 parts / hour after 2-3 hours of dropwise addition. The hydrogen chloride gas generated during the alcoholysis process is absorbed by spraying water to form solution A.
[0069] Then, 15-18 parts by weight of methanol as a co-solvent and an equal amount of urea are gradually added to solution A, and the neutralization temperature is 42°C-50°C, and the neutralization time is 0.5 hours to neutralize the hydrochloric acid in the material. After layering, a crude high-boiling silicone oil is obtained, and the pH value is 4-5. Then, 1.0-1.5 parts by weight of 27% ammonia water is added, and the neutralization is continued to make the pH value 6-8;
[0070] Subsequently, the neutralized solution A is filtered and then the first olefin is added dropwise to carry out a first heat preservation reaction; chloroplatinic acid catalyst is added, and the second olefin is added dropwise to carry out a second heat preservation reaction; after distillation, an alkyl-modified polysiloxane alkane liquid is obtained;
[0071] Then, the dispersant and the co-surfactant are respectively added to the prepared alkyl-modified polysiloxane base liquid and stirred evenly to obtain a mixed organic matter; (the stirring time is 15 minutes; the dispersant is dodecyl betaine, the co-surfactant is a mixture of butanol and acrylamide in a ratio of 1:2, the volume ratio of the dispersant to the co-surfactant is 40:60, and the amount of the stabilizer composed of the dispersant and the co-surfactant is 1% of the mass of the immersed nano-circulation working fluid; the amount of the alkyl-modified polysiloxane base liquid added is 94% of the mass of the immersed nano-circulation working fluid);
[0072] Finally, the nanoparticle mixture is added to the mixed organic matter, ultrasonically oscillated for 5 hours at a frequency of 25KHz, and then left to stand for 12 hours to obtain an immersion nano-circulation working fluid based on alkyl-modified polysiloxane. (Through high-precision mechanical grinding, and then through oxidation, pyrolysis, plasma, laser ablation, laser pyrolysis and other methods, the core is formed in the steam and finally crystallized to form γ-Al2O3 nanoparticles, and the same method is used to form SiO2 nanoparticles. The two nanoparticles are shaken and stirred and mixed in a plasma ultrasonic oscillator at a frequency of 25KHz. The shaking and stirring mixing time is 10 hours to obtain a nanoparticle mixture, that is, a stable γ-Al2O3 and SiO2 mixed organic nanoparticles)
[0073] The prepared alkyl-modified polysiloxane immersed nano-circulating working fluid has high thermal conductivity and increased Prandtl number during the flow heat exchange process. At the same time, the addition of nanoparticles breaks the flow wall boundary between the alkyl-modified polysiloxane base liquid and the tube wall, which greatly increases the disturbance-enhanced heat transfer. According to the analysis of the measuring points, the prepared alkyl-modified polysiloxane immersed nano-circulating working fluid has a 20% increase in unit heat transfer efficiency and a 59% increase in thermal conductivity compared with pure polysiloxane. According to the analysis of multiple experimental measuring points. The thermal conductivity increased from 0.11W / mK of the original polysiloxane base liquid to 0.175W / mK; the kinematic viscosity increased from 10mm 2 / s increased to 11mm 2 / s; specific heat capacity increased from 1.6J / kg℃ to 1.8J / kg℃.
[0074] Embodiment 5:
[0075] In this embodiment, the mass percentages of the components of the alkyl-modified polysiloxane-based submerged nano-circulation working fluid are: 92% alkyl-modified polysiloxane base liquid, 5.5% nanoparticle mixture with a particle size of 100 nm (including γ-Al2O3 nanoparticles and SiO2 nanoparticles), 1.5% dispersant, and 1% surfactant.
[0076] The preparation method is as follows:
[0077] First, add 100 parts by weight of high-boiling organosilicon into the reaction kettle at 20°C-25°C, then dropwise add 30-40 parts by weight of raw material methanol with a weight percentage of 80%-90%, and dropwise add for 6-8 hours. The initial dropwise addition rate is 3 parts / hour, and gradually increases to 10 parts / hour after 2-3 hours of dropwise addition. The hydrogen chloride gas generated during the alcoholysis process is absorbed by spraying water to form solution A.
[0078] Then, 15-18 parts by weight of methanol as a co-solvent and an equal amount of urea are gradually added to solution A, and the neutralization temperature is 42°C-50°C, and the neutralization time is 0.5 hours to neutralize the hydrochloric acid in the material. After layering, a crude high-boiling silicone oil is obtained, and the pH value is 4-5. Then, 1.0-1.5 parts by weight of 27% ammonia water is added, and the neutralization is continued to make the pH value 6-8;
[0079] Subsequently, the neutralized solution A is filtered and then the first olefin is added dropwise to carry out a first heat preservation reaction; chloroplatinic acid catalyst is added, and the second olefin is added dropwise to carry out a second heat preservation reaction; after distillation, an alkyl-modified polysiloxane alkane liquid is obtained;
[0080] Then, the dispersant and the co-surfactant are respectively added to the prepared alkyl-modified polysiloxane base liquid and stirred evenly to obtain a mixed organic matter; (the stirring time is 15 minutes; the dispersant is dodecyl betaine, the co-surfactant is a mixture of butanol and acrylamide in a ratio of 1:2, the volume ratio of the dispersant to the co-surfactant is 40:60, and the amount of the stabilizer composed of the dispersant and the co-surfactant is 1% of the mass of the immersed nano-circulation working fluid; the amount of the alkyl-modified polysiloxane base liquid added is 94% of the mass of the immersed nano-circulation working fluid);
[0081] Finally, the nanoparticle mixture is added to the mixed organic matter, ultrasonically oscillated for 5 hours at a frequency of 25KHz, and then left to stand for 12 hours to obtain an immersion nano-circulation working fluid based on alkyl-modified polysiloxane. (Through high-precision mechanical grinding, and then through oxidation, pyrolysis, plasma, laser ablation, laser pyrolysis and other methods, the core is formed in the steam and finally crystallized to form γ-Al2O3 nanoparticles, and the same method is used to form SiO2 nanoparticles. The two nanoparticles are shaken and stirred and mixed in a plasma ultrasonic oscillator at a frequency of 25KHz. The shaking and stirring mixing time is 10 hours to obtain a nanoparticle mixture, that is, a stable γ-Al2O3 and SiO2 mixed organic nanoparticles)
[0082] The prepared alkyl-modified polysiloxane immersed nano-circulating working fluid has high thermal conductivity and increased Prandtl number during the flow heat exchange process. At the same time, the addition of nanoparticles breaks the flow wall boundary between the alkyl-modified polysiloxane base liquid and the tube wall, which greatly increases the disturbance-enhanced heat transfer. According to the analysis of the measuring points, the prepared alkyl-modified polysiloxane immersed nano-circulating working fluid has a 48% increase in unit heat transfer efficiency and a 120% increase in thermal conductivity compared with pure polysiloxane. According to the analysis of multiple experimental measuring points. The thermal conductivity increased from 0.11W / mK of the original polysiloxane base liquid to 0.243W / mK; the kinematic viscosity increased from 10mm 2 / s increased to 14mm 2 / s; specific heat capacity increased from 1.6J / kg℃ to 1.95J / kg℃.
[0083] The basic performance indicators of the immersed nano-circulation working fluid of the alkyl-modified polysiloxane prepared above were tested, specifically including: referring to the GB / T265 standard, the 40°C kinematic viscosity of the immersed nano-circulation working fluid of the alkyl-modified polysiloxane was tested; referring to the GB / T1884 standard, the density of the immersed nano-circulation working fluid of the alkyl-modified polysiloxane was tested; referring to the ASTMD7896 standard, the thermal conductivity of the immersed nano-circulation working fluid of the alkyl-modified polysiloxane was tested; referring to ASTME1269-2011, the specific heat capacity of the immersed nano-circulation working fluid of the alkyl-modified polysiloxane was tested; the specific test results are shown in Table 1:
[0084] Table 1
[0085]
[0086]
[0087] It can be seen from the data in Table 1 that the thermal conductivity of the immersed nano-circulation working fluids of the embodiments and the comparative examples (pure alkyl-modified polysiloxane) of embodiments 1 to 5 is at least 40% higher than that of the comparative example, and the thermal conductivity of embodiment 5 is as high as 0.243 W / m K; the specific heat capacity of embodiments 1 to 5 is at least 30% higher than that of the comparative example, and the thermal conductivity of embodiment 5 is as high as 1.95 W / m K; compared with the kinematic viscosity of the comparative example 10 mm 2 / s) kinematic viscosity has increased slightly, but the overall heat transfer system still has good flow heat dissipation; from the experimental test results of thermal conductivity, it can be seen that with the addition of nanoparticle concentration, the microstructure of the original alkyl modified polysiloxane has indeed changed, breaking the original flow heat transfer boundary and strengthening the heat transfer. The smaller the nanoparticle concentration and particle size, the better the dispersion and enhanced heat transfer effect. However, too high nanoparticle concentration will increase the kinematic viscosity, thereby increasing the pump power of the cooling system and causing pipeline deposition.
[0088] An alkyl-modified polysiloxane-based immersed nano-circulating working fluid of the present invention comprises 0.005-11.5% of a nanoparticle mixture, 88.0%-99.5% of an alkyl-modified polysiloxane base liquid, 0.05-0.09% of a dispersant and 0.5-15% of a co-surfactant; the nanoparticle mixture comprises γ-Al2O3 nanoparticles and SiO2 nanoparticles, and the alkyl-modified polysiloxane base liquid is firstly obtained for standby use; then the dispersant and the co-surfactant are respectively added to the alkyl-modified polysiloxane and stirred evenly to obtain a mixed organic matter; finally, the nanoparticle mixture is added to the mixed organic matter, and ultrasonic oscillation is performed at a frequency of 25-60KHz for 5-24 hours to obtain an alkyl-modified polysiloxane-based immersed nano-circulating working fluid, thereby solving the technical problems of low heat dissipation efficiency, high risk of thermal runaway, and failure to simultaneously meet the requirements of high-efficiency heat transfer, antifreeze, insulation and fire prevention in the immersion cooling working fluid in the prior art.
[0089] The present invention modifies polysiloxane, adds a dispersant and a co-surfactant, and adds γ-Al2O3 and SiO2 nanoparticles with a particle size of 10nm and a purity of 99.9% to the formed new mixture, thereby effectively improving the thermal conductivity and anti-corrosion and anti-precipitation properties of the nano-circulating working fluid. The prepared nano-circulating working fluid is suitable for immersion equipment.
[0090] In the immersed nano-circulation working fluid of the alkyl-modified polysiloxane prepared by the present invention, in the nanofluid, the suspended nanoparticles are acted upon by various forces such as Brownian force, thereby generating irregular diffusion; these diffusion phenomena include Brownian diffusion and thermal diffusion, etc.; the tiny movement of the nanoparticles leads to micro-convection between the particles and the liquid, and the micro-convection strengthens the energy transfer between the particles and the liquid, thereby improving the heat transfer efficiency per unit area of the nanofluid.
[0091] Since the thermal conductivity of solid nanoparticles is much better than that of liquids, the addition of the selected non-conductive nanoparticles changes the microstructure of the alkyl-modified polysiloxane base liquid, promotes the energy transfer of the nano-circulating working fluid coolant inside the lithium iron phosphate battery PACK, improves the thermal conductivity and Prandtl number, and significantly enhances the enhanced flow boiling heat transfer effect between the inside and outside of the lithium iron phosphate battery PACK.
[0092] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.
Claims
1. An immersion nano-circulation working fluid based on alkyl-modified polysiloxane, characterized in that: The invention comprises 0.005-11.5% of a nanoparticle mixture, 88.0%-99.5% of an alkyl-modified polysiloxane liquid, 0.05-0.09% of a dispersant and 0.5-15% of a co-surfactant; The nanoparticle mixture includes γ-Al2O3 nanoparticles and SiO2 nanoparticles.
2. The submerged nano-circulation working fluid based on alkyl-modified polysiloxane according to claim 1, characterized in that: The nanoparticle mixture has a particle size of 10-100 nm and a purity of 99.9%.
3. The submerged nano-circulation working fluid based on alkyl-modified polysiloxane according to claim 2, characterized in that: The dispersant is one of a zwitterionic surfactant and a nonionic surfactant.
4. The submerged nano-circulation working fluid based on alkyl-modified polysiloxane according to claim 3, characterized in that: The co-surfactant is a mixture of butanol and acrylamide in a ratio of 1:
2.
5. The submerged nano-circulation working fluid based on alkyl-modified polysiloxane according to claim 4, characterized in that: The dispersant zwitterionic surfactant includes dodecyl betaine, dodecyl propyl betaine and alkyl glycoside.
6. The submerged nano-circulation working fluid based on alkyl-modified polysiloxane according to claim 5, characterized in that: The dispersant nonionic surfactant is polyvinyl pyrrolidone.
7. A method for preparing an immersion-type nano-circulation working fluid based on an alkyl-modified polysiloxane, for preparing the immersion-type nano-circulation working fluid based on an alkyl-modified polysiloxane as claimed in claim 6, characterized in that: Step 1, first obtain an alkyl-modified polysiloxane base liquid for use; Step 2: adding the dispersant and the co-surfactant to the alkyl-modified polysiloxane respectively and stirring evenly to obtain a mixed organic matter; Step 3: Finally, the nanoparticle mixture is added to the mixed organic matter, and ultrasonically oscillated for 5-24 hours at a frequency of 25-60 KHz to obtain an immersion nano-circulation working fluid based on alkyl-modified polysiloxane.
8. The method for preparing an immersion nano-circulation working fluid based on alkyl-modified polysiloxane according to claim 7, characterized in that: In step 2, the dispersant and the co-surfactant are added to the alkyl-modified polysiloxane and stirred to obtain a mixed organic matter: The stirring time is 30-180 minutes, and after the mixing is completed, it is allowed to stand for 30-60 minutes.
Citation Information
Patent Citations
Nano cycle working medium used for middle and low temperature organic Rankine cycle
CN105255452A
Alkyl methylsiloxane liquid immersion cooling medium
CN116438502A
Long-chain alkyl modified polysiloxane and preparation method thereof
CN117924709A